Impact of Coronavirus Disease 2019 Pandemic on Pediatric Out-of-Hospital Cardiac Arrest in the Emergency Department - Chen, Chun-Yu; Lee, En-Pei; Chang, Yu-Jun; Yang, Wen-Chieh; Lin, Mao-Jen; Wu, Han-Ping (Frontiers in Pediatrics, 2022)
Background: Out-of-hospital cardiac arrest (OHCA) in children is a critical condition with poor prognosis. After the coronavirus disease 2019 (COVID-19) pandemic developed, the epidemiology and clinical characteristics haves been changed in pediatric emergency department (PED) visits. The study aimed to analyze the impact of COVID-19 pandemic in pediatric OHCA in the PED. Methods: From January 2018 to September 2021, we retrospectively collected children aged 18 years or younger with a definite diagnosis of OHCA admitted to the PED. The following data, including demographics, pre-/in-hospital information, treatment modalities, and outcomes of interest included sustained return of spontaneous circulation (SROSC) and survival to hospital-discharge (STHD were analyzed and compared between the periods before and after COVID-19 pandemic outbreak. Results: A total of d 97 patients with OHCA (68 boys and 29 girls) sent to the PED were enrolled in our study. Of all cases, 60 cases (61.9%) occurred in the pre-pandemic period, and 37 cases were during the pandemic period. The most common age group was infants (40.2%) (P =0.018). Asystole was the most predominant cardiac rhythm (72.2%, P =0.048). About 82.5% were transferred by the emergency medical services (EMS), 62 cases (63.9%) gained sustained return of spontaneous resuscitation (SROSC) and 25 (25.8%) were STHD. During the COVID-19 pandemic period, non-trauma OHCA children had significantly shorter survival duration and prolong EMS scene interval (both p< 0.05). Conclusions: OHCA in children is relatively uncommon but critical with a high mortality rate. During the COVID-19 pandemic period, children with OHCA had significant shorter survival duration than that in the pre-pandemic period). The COVID-19 pandemic has changed the nature of PED visits and affect related factors for ROSC and STHD in pediatric OHCA.